PENERAPAN MODEL PEMBELAJARAN EXPLICIT INSTRUCTION DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS IV PADA PEMBELAJARAN FIQIH DI SEKOLAH DASAR ISLAM TERPADU ALMAWADDAH WARRAHMAH KOLAKA - lntan Permata Sari; Abd Haris Nasution; Muh Iqbal (Universitas Sains Islam Al Mawaddah Warrahmah Kolaka, 2025)
The lack of students in paying attention to the teacher when explaining learning is one of them, namely the strategy and application of learning models that are not appropriate and varied. So that students look bored and pay less attention to the teacher in the learning process, so that it can refer to the learning outcomes of students who are less than optimal. Therefore the author tries to apply the Explicit Instruction method (direct teaching) Explicit Instruction model is an approach or learning model designed to improve student learning outcomes. The title of the research to be carried out is. “The Application of the Explicit Instruction Teaching Model in Improving the Learning Outcomes of Class IV Students in Fiqh Learning at SDIT Al-Mawaddah Warrahmah Kolaka”.he problems that can be raised in this study are How is the application of the Explicit Instruction learning model in class IV SDIT Al-Mawaddah Warrahmah Kolaka and How is the improvement of student learning outcomes in Fiqh subjects through the application of the Explicit Instruction learning model in class IV SDIT Al Mawar Kolaka. While the purpose of this study is to find out how the application of the Explicit Instructuon learning model in Fiqh class IV SDIT Al Mawar Kolaka and to find out how the improvement of Fiqh learning outcomes with the application of the Explicit Instruction learning model in class IV SDIT Al Kolaka.The type of research in this study is classroom action research with a qualitative approach. The number of samples in this study were 16 students. Data collection techniques in this study used observation sheets, interviews, tests and documentation. This research is said to be successful if the completeness of student learning outcomes reaches 75% or as a whole has reached the KKM 75 value in Fiqh subjects in the use of the Expilicit Instruction learning model. The application of the Explicit Instruction learning model in cycle I shows an increase but there are still some students who have not maximized the learning outcomes . However, students have started to be very good in their activeness or enthusiasm for asking and answering questions given, it can be seen that the indicator scores experienced by students have increased compared to the initial observation in the pre-cycle before the Explicit Instruction learning model is applied . Then continued in cycle II, where in cycle II students have reached 75% or as a whole have reached the KKM score of 75 in Fiqh subjects in the use of the Expilicit Instruction learning model . The results of this study concluded that there was an increase in student learning outcomes when learning using the application of the Explicit Instruction learning model according to procedures. This is evident in the percentage results of cycle I, which reached 73%, while the percentage results of cycle II reached 85%.